Augmented and Virtual Reality Second International Conference, AVR 2015, Lecce, Italy, August 31 - September 3, 2015, Proceedings - De Paolis, Lucio Tommaso; Mongelli, Antonio; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the Second International Conference on Augmented and Virtual Reality, AVR 2015, held in Lecce, Italy, in September 2015. The 32 papers and 8 short papers presented were carefully reviewed and selected from 82 submissions. The SALENTO AVR 2015 conference brings together a community of researchers from academia and industry, computer scientists, engineers, and physicians in order to share points of views, knowledge, experiences, and scientific and technical results related to state-of-the-art solutions and technologies on virtual and augmented reality applications for medicine, cultural heritage, education, industrial sectors, as well as the demonstration of advanced products and technologies.
Tutorials -- Research, Prototyping, and Product Development of Medical Simulation Applications Using the SOFA Framework.-Cultural Heritage Innovation Design: what Caught my Eye -- Keynote Speeches -- How Touch and Smell Enhance the Realism of our Virtual Experiences -- Collaborative Interactions within Immersive Environments: Advantages, Drawbacks and Current Research Issues on Multi-Stereoscopic CAVE-like Setups -- Touchless Interaction in Surgery: the Medical Imaging Toolkit Experience -- Virtual Museums Interacting and Augmenting Cultural Heritage: an European Perspective -- Applications in Cultural Heritage -- Integrated Technologies for Museum Communication and Interactive Apps in the PON DiCet Project -- "Social Heritage" Augmented Reality Application to Heritage Education -- Making Visible the Invisible. Augmented Reality Visualization for 3D Reconstructions of Archaeological Sites -- Advanced interaction with Paintings by Augmented Reality and High Resolution Visualization. A real Case Exhibition -- Cloud Computing and Augmented Realty for Cultural Heritage -- Augmented and Mixed Reality -- Accurate on Site Georeferenced Subsurface Utility Model Visualisation -- The Augmented Reality Story Book Project: A Collection of Balinese Miths and Legends -- ARBS: An Interactive and Collaborative System for Augmented Reality Books -- Robust Model Based Tracking using Edge Mapping and Refinement -- Augmented Reality, Embodied Cognition and Learning -- OscARsWelt: A Collaborative Augmented Reality Game -- Device Registration for 3D Geometry-based User-Perspective Rendering in Hand-Held Video See-Through Augmented Reality -- Creativity Support in Projection-based Augmented Environments -- IMU Drift reduction for Augmented Reality Applications -- Applications in Medicine -- Serious games for rehabilitation using head-mounted display and haptic devices -- VR-based Serious Game Designed for Medical Ethics Training -- Scalable Medical Viewer for Virtual Reality Environments -- A Pre-Operative Planning Module for an Augmented Reality Application in Maxillo-Facial Surgery -- Augmented Reality Assisted Brain Tumor Extraction in Mice -- Applications in Industry and Robotics -- A Virtual Prototyping Platform to Improve CAE Analysis Workflow -- A Proposed Hardware-Software Architecture for Virtual Reality in Industrial Applications -- Using Haptic Forces Feedback for immersive and interactive simulation in industrial context -- A Flexible AR-based Training System for Industrial Maintenance -- Training in VR: a preliminary study on learning Assembly/Disassembly sequences -- Applying Aesthetic Rules in Virtual Environments by means of Semantic Web Technologies -- Bilateral Control of a Robotic Arm Through Brain Signals -- Interfaces -- Natural user interfaces for virtual character full body and facial animation in immersive virtual worlds -- ARTworks: an Augmented Reality Interface as an aid for Restoration Professionals -- Design and preliminary evaluation of free-hand travel techniques for wearable immersive virtual reality systems with egocentric sensing -- Perception of Basic Emotions from Facial Expressions of Dynamic Virtual Avatars -- Bridging Offline and Online World through Augmentable Smart Glass Interfaces -- Touchless Interaction for Command and Control in Military Operations -- Short Papers -- Development of a framework to support Virtual Review within complex-product lifecycle management. 3D Physics Virtual Laboratory as a Teaching Platform -- Experiences in Development of an Augmented Reality Dressing Room -- Development of a Virtual laboratory for investigating the interaction of materials with plasma -- Aspects Concerning Algorithms of VRML Surfaces' Generation -- Towards a Framework for Information Presentation in Augmented Reality for the Support of Procedural Tasks -- A dynamic-oriented Decision Support System for group Interview Knapsack Problem -- Virtual Reality as Cross-Domain Language in Collaborative Environments.
Keywords: Computer science; User interfaces (Computer systems).; Computer simulation; Computer graphics; Application software; Education -- Data processing; Computer Science; Computer Imaging, Vision, Pattern Recognition and Graphics; User Interfaces and Human Computer Interaction; Computer Applications; Simulation and Modeling; Computers and Education